Organobase-catalyzed three-component reactions for the synthesis of 4H-2-aminopyrans, condensed pyrans and polysubstituted benzenes - Moustafa, Moustafa Sherief; Al-Mousawi, Saleh Mohammed; Selim, Maghraby Ali; Mosallam, Ahmed Mohamed; Elnagdi, Mohamed Hilmy (Beilstein Journal of Organic Chemistry, 2014)
Novel routes for the preparation of 2-amino-4H-pyran-3-carbonitrile 9, amino-arylbenzoic acid ester derivatives 13a,b, 2-aminotetrahydro-4H-chromene-3-carbonitrile 18, 3-amino-4-cyanotetrahydronaphthalene-2-carboxylic acid ester 26 and 4-amino-3,5-dicyanophthalic acid ester derivatives 37a–c were developed. The synthetic methods utilize one-pot reactions of acetylene carboxylic acid esters, α,β-unsaturated nitriles and/or active methylenenitriles in the presence of L-proline or DABCO. Plausible mechanisms are suggested for the formation of the products. Finally, these compounds were used for the efficient synthesis of 6-amino-5-cyanonicotinic acid ester derivatives 31a,b, ethyl 4-amino-5H-pyrano[2,3-d]pyrimidine-6-carboxylates 33a,b, 4-amino-6H-pyrrolo[3,4-g]quinazoline-9-carbonitrile 39, and 1,7-diamino-6-(N'-hydroxycarbamimidoyl)-3-oxo-5-phenyl-3H-isoindole-4-carboxylate (40).
Keywords: aminopyranes; arylbenzoic acid; DABCO; L-proline; multicomponent; tetrahydronaphthalene; three-component reaction